Measurement report: A multi-year study on the impacts of Chinese New Year celebrations on air quality in Beijing, China - B. Foreback; B. Foreback; L. Dada; K. R. Daellenbach; C. Yan; C. Yan; L. Wang; B. Chu; B. Chu; Y. Zhou; T. V. Kokkonen; T. V. Kokkonen; et al. (Atmospheric Chemistry and Physics, 2022)
This study investigates the influence of the Chinese New Year (CNY) celebrations on local air quality in Beijing from 2013 through 2019. CNY celebrations include burning of fireworks and firecrackers, which consequently has a significant short-term impact on local air quality. In this study, we bring together comprehensive observations at the newly constructed Aerosol and Haze Laboratory at Beijing University of Chemical Technology – West Campus (BUCT-AHL) and hourly measurements from 12 Chinese government air quality measurement stations throughout the Beijing metropolitan area. These datasets are used together to provide a detailed analysis of air quality during the CNY over multiple years, during which the city of Beijing prohibited the use of fireworks and firecrackers in an effort to reduce air pollution before CNY 2018. Datasets used in this study include particulate matter mass concentrations (PM2.5 and PM10), trace gases (NOx, SO2, O3, and CO), and meteorological variables for 2013–2019; aerosol particle size distributions; and concentrations of sulfuric acid and black carbon for 2018 and 2019. Studying the CNY over several years, which has rarely been done in previous studies, can show trends and effects of societal and policy changes over time, and the results can be applied to study problems and potential solutions of air pollution resulting from holiday celebrations. Our results show that during the 2018 CNY, air pollutant concentrations peaked during the CNY night (for example, PM2.5 reached a peak around midnight of over 250 µg cm−3, compared to values of less than 50 µg cm−3 earlier in the day). The pollutants with the most notable spikes were sulfur dioxide, particulate matter, and black carbon, which are emitted in burning of fireworks and firecrackers. Sulfuric acid concentration followed the sulfur dioxide concentration and showed elevated overnight concentration. Analysis of aerosol particle number size distribution showed direct emissions of particles with diameters around 100 nm in relation to firework burning. During the 2019 CNY, the pollution levels were somewhat lower (PM2.5 peaking at around 150 µg cm−3 on CNY compared to values around 100 µg cm−3 earlier in the day), and only minor peaks related to firework burning were observed. During both CNYs 2018 and 2019 secondary aerosol formation in terms of particle growth was observed. Meteorological conditions were comparable between these 2 years, suggesting that CNY-related emissions were less in 2019 compared to 2018. During the 7-year study period, it appears that there has been a general decrease in CNY-related emissions since 2016. For example, the peak in PM2.5 in 2016 was over 600 µg cm−3, and in the years following, the peak was less each year, with a peak around 150 µg cm−3 in 2019. This is indicative of the restrictions and public awareness of the air quality issues having a positive effect on improving air quality during the CNY. Going into the future, long-term observations will offer confirmation for these trends.